Staying alive? Navigating Uncertainty in Cancer in Childhood - Løvschal-Nielsen, Pia; Andersen, Rikke Sand; Meinert, Lotte (Tidsskrift for Forskning i Sygdom og Samfund, 2018)
Abstract In this article we explore how institutions and individuals in Denmark deal with uncertainty of cancer in childhood. Based on a seven months ethnographic fieldwork conducted on a paediatric oncology ward from 2011-2013, we examine how uncertainty and insecurities manifest in the interface between cancer treatment and childhood in the Danish welfare state. We develop our argument theoretically with the American pragmatist philosophy and its ideas that people are responding to a hazardous world in constant transformation. Through a focus on micro practices we explore how uncertainty manifests especially for children and their families, and how they navigate insecurities. Important collective attempts to create some measure of certainty and security are done in treatment practices, but we argue that biomedical practices dealing with uncertainty of cancer paradoxically give rise to existential and social uncertainty among children and their families, which they struggle with, also after the end of cancer treatment, as long-term social effects of cancer in childhood. We suggest that more attention could be paid to assist children in dealing with uncertainty and insecurities imminent to being in cancer treatment in the Danish welfare state and the social effects of this.